Filosofi, Konsep Hasil Penggunaan Teknik Modeling Dalam Bimbingan Kelompok dan Field Trip Industry untuk Meningkatkan Motivasi Berwirausaha - Naili Faizatis syifa syifa; Basukiyatno; Maufur (Universitas Pancasakti Tegal, 2020)
The puprpose study to determine whether the philosophy, concepts in modeling group guidance and industry field trips can increase entrepreneurial motivation in accordance with the 2013 curriculum. The research method used in this research is descriptive qualitative analysis. The results of the study concluded that modeling techniques and field trip industries could increase students' entrepreneurial motivation. Entrepreneurial motivation is basically an encouragement, interest, and availability to work hard or have a strong will to try maximally to make ends meet without feeling afraid of the risks that will occur, as well as a strong desire to learn from failure, a high heart tendency towards preference. on a thing or activity, without being told